2017
DOI: 10.1370/afm.2060
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Clinical Decision Rules to Diagnose Acute Rhinosinusitis Among Adults in Primary Care

Abstract: PURPOSE To reduce inappropriate antibiotic prescribing, we sought to develop a clinical decision rule for the diagnosis of acute rhinosinusitis and acute bacterial rhinosinusitis.METHODS Multivariate analysis and classification and regression tree (CART) analysis were used to develop clinical decision rules for the diagnosis of acute rhinosinusitis, defined using 3 different reference standards (purulent antral puncture fluid or abnormal finding on a computed tomographic (CT) scan; for acute bacterial rhinosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Two studies reported the accuracy of combinations of signs and symptoms for the diagnosis of ABRS (Table 5). 25,36 Berg proposed a 4-item score using a reference standard of purulent antral puncture fluid. The score discriminated well: those with a score or 3 or 4 findings present had a LR of 7 for ABRS, while those with ≤1 findings present had a LR of 0.06.…”
Section: Acute Bacterial Rhinosinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported the accuracy of combinations of signs and symptoms for the diagnosis of ABRS (Table 5). 25,36 Berg proposed a 4-item score using a reference standard of purulent antral puncture fluid. The score discriminated well: those with a score or 3 or 4 findings present had a LR of 7 for ABRS, while those with ≤1 findings present had a LR of 0.06.…”
Section: Acute Bacterial Rhinosinusitismentioning
confidence: 99%
“…25 The most recently reported clinical decision rule used 5 signs or symptoms plus C-reactive protein (see Table 5 for scoring details) to identify patients at low risk (n = 77, 16%), moderate risk (n = 75, 49%), or high risk (n = 23, 73%) for ABRS using positive bacterial culture of antral puncture fluid as the reference standard. 36 Unfortunately, none of the above scores have been prospectively validated.…”
Section: Acute Bacterial Rhinosinusitismentioning
confidence: 99%
“…15 However, both rules still require prospective validation in different populations, and an assessment of their impact on prescribing. Held and colleagues developed a simple CDR to rule out pneumonia in Swiss outpatients with acute cough, which was then validated in a separate Swiss population.…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…13 In addition to offering symptomatic relief, previous strategies to reduce antibiotic prescription in acute sinusitis have included patient, prescriber, and public education (including in-office posters); enhancing communication between clinician and patient regarding withholding of antibiotics; implementation of clinical pathways; prescribing of delayed/reserved antibiotic prescriptions; and efforts to improve differentiation of bacterial versus viral sinusitis at the time of patient visit. 2,8,[14][15][16][17][18] These efforts include clinical decision rules, 16 C-reactive protein point-of-care testing, 17 and the potential for procalcitonin point-of-care testing. 18 The latter two actions, along with clinical shared decision-making, were noted in a Cochrane review as exhibiting moderate-quality evidence, suggesting efficacy in reducing antibiotic prescriptions for upper respiratory tract infections (URI).…”
Section: Improper Antibiotics Usementioning
confidence: 99%